Quality control criteria for positioning mammography exams: an integrative review (Research, Society and Development, 2023)
Objective: To analyze the production in the literature on mammographic positioning and evaluations of clinical quality control in mammography exams. Method: Integrative review carried out in the SCOPUS, SCIELO, PUBMED/MEDLINE, LILACS, BDENF, CINAHL, EMBASE, COCHRANE Library, WEB OF SCIENCE databases. The search strategy was defined with the help of a librarian. The selection of research articles was performed first by reading the titles and abstracts and then by reading the full article. Results: As a result of this research, we obtained 8 articles that passed the sieve of exclusion and inclusion criteria, containing the characteristics of the publications (title, year, country, authors, objectives and main results). Finals considerations: The quality standards for an effective positioning in mammography exams are well defined in all studies, it is important to mention the importance of a new image evaluation system, the PGMI (perfect, good, adequate and inadequate) is being used to assist in the elimination of subjectivity in the evaluation of quality criteria in the positioning of exams. In Brazil, we did not find studies published in the last five years related to quality, proving the need for deeper actions to understand the challenges that may be encountered.